1999
DOI: 10.1021/np980520w
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformation of Sesquiterpene Lactones by the Fungi Cunninghamella echinulata and Rhizopus oryzae

Abstract: Incubations of the fungi Cunninghamella echinulata and Rhizopus oryzae with the sesquiterpene lactones (+)-costunolide (1), (+)-cnicin (2), (+)-salonitenolide (3), (-)-dehydrocostuslactone (4), (-)-lychnopholide (5), and (-)-eremantholide C (6) were perfomed. Incubation of 1 with C. echinulata afforded ∆ 11(13)dihydrogenation and ∆ 1(10) -epoxidation products (7-10). C. echinulata also hydrolyzed the side chain of 2, and transformed 4 into (+)-11R,13-dihydrodehydrocostuslactone (12), a new natural product. R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
2
23
0
1
Order By: Relevance
“…Since biotransformations are a choice tool to insert hydroxyl groups in terpenes (Aleu et al 1999, Barrero et al 1999, Takahashi et al 2014, compound 1 was fed to M. plumbeus aiming at obtaining hydroxylated trachylobane derivatives for biological screening as AChE inhibitors. After nine days of biotransformation, TLC profile of the resulting organic extract showed presence of biotransformation products, both of them more polar than starting material 1.…”
Section: Resultsmentioning
confidence: 99%
“…Since biotransformations are a choice tool to insert hydroxyl groups in terpenes (Aleu et al 1999, Barrero et al 1999, Takahashi et al 2014, compound 1 was fed to M. plumbeus aiming at obtaining hydroxylated trachylobane derivatives for biological screening as AChE inhibitors. After nine days of biotransformation, TLC profile of the resulting organic extract showed presence of biotransformation products, both of them more polar than starting material 1.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, degradation of the isoalantolactone was very rapid and 37% of the lactone was not extracted immediately after incorporation into the soil. Similarly, several studies have reported microbial transformation of costunolide, a sesquiterpene lactone (Clark and Hufford, 1979;Barrero et al, 1999;Ma et al, 2007). Based on these previous studies, adsorption and microbial degradation of phytotoxic allelochemicals from P. hysterophorus residue on organic soil most likely resulted in no effect of the residue on sugarcane.…”
Section: Resultsmentioning
confidence: 99%
“…Although several researchers worldwide have chemically investigated T. diversifolia, compound 2 was isolated only from a Brazilian population [2]. As already mentioned, it should be emphasized that the main enzymatic reactions that Aspergillus promotes in STLs are hydrogenation, hydroxylation, reduction, and acetylation [6,11,15,17,20,27,29,31,39,40]. Interestingly, we have uncovered an unusual epoxidation between C4 and C5; a methoxy group was added at C1, and a C1,C10 ether bridge was formed in the 10-membered ring of 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the crude extract from the leaves of T. diversifolia used in this work had been screened for the presence of 2 by HPLC-DAD analysis, and it was not detected even as a trace. According to Barrero et al [6], epoxidation and hydrogenation reactions of the exocyclic double bond at C11-C13 seem to be the most common processes in the microbial transformation of STLs by filamentous fungi. In order to explain the formation of the epoxide group between C4 and C5 in the biotransformed molecule 2 as well as the methoxylation of C1, we followed the proposal of Onken and Berger [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation